2018
DOI: 10.1093/toxsci/kfy149
|View full text |Cite
|
Sign up to set email alerts
|

Role of YAP Activation in Nuclear Receptor CAR-Mediated Proliferation of Mouse Hepatocytes

Abstract: Constitutive androstane receptor (CAR) is a xenobiotic-responsive nuclear receptor that is highly expressed in the liver. CAR activation induces hepatocyte proliferation and hepatocarcinogenesis in rodents, but the mechanisms remain unclear. In this study, we investigated the association of CAR-dependent cell proliferation with Yes-associated protein (YAP), which is a transcriptional cofactor controlling organ size and cell growth through the interaction with various transcriptional factors including TEA domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 45 publications
2
44
1
Order By: Relevance
“…39) This hypothesis seemed too easy and we soon found that this was not the case but the results were very surprising and interesting (see below), which drove us to start a series of experiments on the involvement of PXR in hepatocyte proliferation. 31,32,34) Single treatment of mice with TCPOBOP increased the number of proliferation marker Ki-67-positive hepatocytes 48 h after the treatment whereas PCN did not, as expected. These findings were confirmed by determining mRNA levels of cell cycle-related genes such as Ccna2, Ccnb1, Mcm2, or Mki67.…”
Section: Fig 1 Association Of Pxr and Car With Hepatocyte Proliferasupporting
confidence: 74%
See 3 more Smart Citations
“…39) This hypothesis seemed too easy and we soon found that this was not the case but the results were very surprising and interesting (see below), which drove us to start a series of experiments on the involvement of PXR in hepatocyte proliferation. 31,32,34) Single treatment of mice with TCPOBOP increased the number of proliferation marker Ki-67-positive hepatocytes 48 h after the treatment whereas PCN did not, as expected. These findings were confirmed by determining mRNA levels of cell cycle-related genes such as Ccna2, Ccnb1, Mcm2, or Mki67.…”
Section: Fig 1 Association Of Pxr and Car With Hepatocyte Proliferasupporting
confidence: 74%
“…To investigate this possibility, we carried out a series of experiments using in vitro and in vivo models. 31,32) We first used immortalized mouse normal hepatocytes, AML12 cells, as an in vitro model. 32) When AML12 cells are cultured in the absence of serum for 48 h, they become synchronized at the G0 phase, and we are able to make the cells enter the cell cycle by culturing them in medium containing serum.…”
Section: Acceleration Of Growth Factor-associated Hepatocyte Prolifermentioning
confidence: 99%
See 2 more Smart Citations
“…Kowalik et al showed that activation of CAR increased nuclear translocation of YAP, which, for the first time, suggests the interaction of the xenobiotic nuclear receptor family member with the Hippo–YAP pathway . Furthermore, Abe et al showed that knockdown or pharmacological inhibition of YAP drastically diminished the CAR‐dependent cell growth and induction of the cell proliferation marker genes . Interestingly, similar to PXR, CAR activation–induced cell proliferation and drug disposition are also detached, as shown by a recent publication from Bhushan et al However, a direct physical interaction between CAR and YAP has not been determined from these studies.…”
mentioning
confidence: 95%